2018
DOI: 10.11613/bm.2018.030502
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width in pregnancy: a systematic review

Abstract: Anisocytosis has been associated with the severity and prognosis of several acute and chronic diseases, as well as physiological conditions such as pregnancy. Anisocytosis is quantified by the red blood cell distribution width (RDW), expressed as the ratio, multiplied by 100, between the standard deviation (SD) of red blood cell volumes and the mean corpuscular volume, or as the SD of erythrocyte volumes (RDW-SD). The aim of the present review was to report the state of the art on the physiological values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
0
31
0
1
Order By: Relevance
“…RDW values of ≤ 12.9 were categorized as normal and values ≥ 13.0 were considered elevated. Stroke severity (NIHSS) was categorized as mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe , and mRS ≪ 2 (0,1, and 2) was defined as a fine outcome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RDW values of ≤ 12.9 were categorized as normal and values ≥ 13.0 were considered elevated. Stroke severity (NIHSS) was categorized as mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe , and mRS ≪ 2 (0,1, and 2) was defined as a fine outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Red cell distribution width (RDW) is a hematologic parameter that indicates the divergence of red blood cell volume. Increases in RDW have been found in different physiological and pathological conditions such as pregnancy, vitamin B12 and folate deficiency, malignancy, idiopathic pulmonary fibrosis and coronary artery disease [7][8][9][10][11][12]. Although RDW was created for the diagnosis of different types of anemia, recent research has revealed its predictive role in cerebrovascular diseases [13].…”
Section: Introductionmentioning
confidence: 99%
“…RDW values of ≤12.9 were categorized as normal and values ≥13.0 were considered elevated. Stroke severity (NIHSS) was categorized as mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe , and mRS <<2 (0,1, and 2) was de ned as a ne outcome.…”
Section: Methodsmentioning
confidence: 99%
“…RDW is a hematologic parameter that indicates the divergence of red blood cell volume. Increases in RDW have been found in different physiological and pathological conditions such as pregnancy, vitamin B12 and folate de ciency, malignancy, idiopathic pulmonary brosis and coronary artery disease (7)(8)(9)(10)(11)(12). Although RDW was created for the diagnosis of different types of anemia, recent research has revealed its predictive role in cerebrovascular diseases (13).…”
Section: Introductionmentioning
confidence: 99%
“…RDW is a hematologic parameter that indicates the divergence of red blood cell volume. Increases in RDW have been found in different physiological and pathological conditions such as pregnancy, vitamin B12 and folate deficiency, malignancy, idiopathic pulmonary fibrosis and coronary artery disease (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%